Case report: Utility, complications, and short-term outcomes in three dogs managed with percutaneous pigtail cystostomy catheters for urethral obstruction - Er, Yanshan; Fick, Meghan E.; Long Mays, Erin (Frontiers in Veterinary Science, 2023)
Objective: To describe the utility, complications and short-term outcomes of three dogs managed with percutaneous pigtail cystostomy catheters placed in the emergency room (ER).Case summary: Three dogs were presented separately to the ER for unalleviated mechanical urethral obstruction secondary to urolithiasis and urethral neoplasia. Retrograde urinary catheterization and urohydropulsion were not successful after multiple attempts. Percutaneous pigtail cystostomy catheters were placed under sedation to achieve temporary urinary diversion and was successful in two of three dogs. Complications encountered include mild abdominal effusion, unsuccessful placement resulting in hemorrhagic abdominal effusion, steatitis and abdominal pain, and kinking of the tube. The two dogs diagnosed with urolithiasis were discharged from the hospital and the dog diagnosed with urethral neoplasia was humanely euthanized due to poor prognosis.New or unique information provided: When successful, placement of pigtail cystostomy catheters allowed for temporary urinary diversion until definitive treatment could be performed and were welltolerated. Short-term outcomes were good. Complications arising from this procedure were common and increased morbidity. The risk of unsuccessful catheter placement may be increased when the procedure is performed in an overconditioned patient or by an inexperienced operator. Careful case selection and risk-benefit analysis should be considered prior to attempting this procedure. Further studies are necessary to evaluate the ideal technique, incidence of complications and outcomes of this procedure.